Turning the tide on female genital mutilation in a high prevalence country: a programmatic data analysis for Sudan's comprehensive health sector response, 2016–2018. Issue 10 (21st October 2022) - Ahmed, Wisal; Puttkammer, Nancy; Gloyd, Stephen; Adam, Amira; Eltayeb, Dalya; Farquhar, Carey
Abstract : Sudan has about 87% of females aged 15–49 years living with female genital mutilation (FGM), mostly performed by midwives (64%). In 2016, the Federal Ministry of Health (FMoH) adopted the WHO's global strategy to stop healthcare providers from performing FGM. Our review of activity reports from 2016 to 2018 found the format of activities (N=95) was mainly meetings (58%) and trainings (31%) with median costs of US$10 645 and US$14 964, respectively. The FMoH (57%) and student/professional associations (25%) implemented activities at national (36%) and state (62%) level. The costs of activities were highest for FMoH compared with student/professional associations and academia, respectively. Sudan addressed WHO's global strategy pillars through FGM-related policies and plans (pillar 1), trainings (pillar 2) and monitoring, evaluation and accountability materials (pillar 3) targeting mainly community midwives (N=16 183) as well as creating supportive legislative and regulatory environment (pillar 4). Governmental funding on training was comparable to donor's resulting into 31% of community midwives trained on FGM complications management. Further, 31% of community midwives signed declarations or petitions to end FGM practice, while 19% were sensitised on punitive administrative measures for conducting FGM. Although Sudan implemented a laudable health sector response to address FGM, there is a need to evaluate the quality and effectiveness of past and ongoing interventions. Particular attention to costs and quality assurance data is essential to identify cost efficient implementation approaches to reach the remaining sizeable number of health professionals to stop their involvement in FGM.